2017
DOI: 10.1021/acs.est.7b03089
|View full text |Cite
|
Sign up to set email alerts
|

Current Stormwater Harvesting Guidelines Are Inadequate for Mitigating Risk from Campylobacter During Nonpotable Reuse Activities

Abstract: Campylobacter is a pathogen frequently detected in urban stormwater worldwide. It is one of the leading causes of enteric disease in many developed countries and is the leading cause of enteric disease in Australia. Prior to harvesting stormwater, adequate treatment is necessary to mitigate risks derived from such harmful pathogens. The goal of this research was to estimate the health risks associated with the exposure to Campylobacter when harvesting urban stormwater for toilet flushing and irrigation activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Additionally, uses and their relative frequencies are different for US populations compared to those from Australia [6]. C. jejuni is a fecal-oral pathogen that can be of concern for food crop irrigation or toilet flushing using rainwater [58]. Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, uses and their relative frequencies are different for US populations compared to those from Australia [6]. C. jejuni is a fecal-oral pathogen that can be of concern for food crop irrigation or toilet flushing using rainwater [58]. Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported high risks due to Campylobacter spp. through reuse of stormwater in the Netherlands (Sales-Ortells and Medema, 2015) and Australia (Murphy et al, 2017). These studies, however, only measured members of the genus Campylobacter to estimate risk.…”
Section: Pathogens In Stormwatermentioning
confidence: 99%
“…The risks from potable and non-potable uses of stormwater in Table 3 varied substantially depending on the target pathogen and exposure scenario. Risks were considered highest for viral pathogens, in most cases exceeding risk benchmarks for potable and non-potable use with the exception of toilet flushing in some cases Murphy et al, 2017). The studies summarized in Table 3 indicate that potable and non-potable exposures to stormwater are likely to exceed water quality targets [e.g.…”
Section: Health Risk Assessment Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 It has been known for decades that urban stormwater is a contributor to the impairment of water quality. 14 Thus, monitoring and management programs have focused on conventional stormwater pollutants such as total suspended solids (TSS), [15][16][17] nutrients, 15,18 pathogens, [19][20][21] metals, [15][16][17][18]22,23 polycyclic aromatic hydrocarbons (PAHs), 17,[24][25][26] polychlorinated biphenyls, 27 and certain pesticides. 28,29 While stormwater research has long concentrated on particle-associated pollutants, a review article by LeFevre et al 18 highlighted the importance of dissolved stormwater pollutants (mainly nutrients, toxic metals, and hydrocarbons) and identified a major lack of knowledge about hyphil-TrOCs.…”
Section: Introductionmentioning
confidence: 99%